2017
DOI: 10.1016/j.ejogrb.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of gynaecology teaching associates in teaching pelvic examination to medical students: a randomised controlled trial

Abstract: GTA teaching of female pelvic examination at the start of undergraduate medical student O&G clinical placements improves their confidence and competence compared with conventional pelvic manikin based teaching. GTAs should be introduced into undergraduate medical curricula to teach pelvic examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
0
21
0
4
Order By: Relevance
“…La Tabla 3 muestra los resultados de los estudios incluidos en esta revisión sistemática. Los efectos intragrupo se midieron en cinco estudios (Aper et al, 2012;Becker et al, 2006;Hong et al, 2014;Janjua et al, 2017;Koponen et al, 2012) y se descubrió que el grupo que realizó la simulación de pacientes estandarizados mostró mejoras en la adquisición de conocimiento (Becker et al, 2006;Kim & Shin, 2016), self-efficacy (Aper et al, 2012;Janjua et al, 2017), desarrollo de habilidades comunicativas (Koponen et al, 2012) (Brady et al, 2015;Jansson et al, 2014;Kesten, 2011;Kim & Shin, 2016;Lee Chin et al, 2014), aprendizaje de la práctica clínica (Brady et al, 2015;Elley et al, 2012;Janjua et al, 2017;Jansson et al, 2014;Kim & Shin, 2016), desarrollo de habilidades comunicativas (Elley et al, 2012;Kessler et al, 2015;Kesten, 2011;Koponen et al, 2012;Schlegel et al, 2012;Zavertnik et al, 2010), y autoeficacia (Aper et al, 2012;Janjua et al, 2017).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…La Tabla 3 muestra los resultados de los estudios incluidos en esta revisión sistemática. Los efectos intragrupo se midieron en cinco estudios (Aper et al, 2012;Becker et al, 2006;Hong et al, 2014;Janjua et al, 2017;Koponen et al, 2012) y se descubrió que el grupo que realizó la simulación de pacientes estandarizados mostró mejoras en la adquisición de conocimiento (Becker et al, 2006;Kim & Shin, 2016), self-efficacy (Aper et al, 2012;Janjua et al, 2017), desarrollo de habilidades comunicativas (Koponen et al, 2012) (Brady et al, 2015;Jansson et al, 2014;Kesten, 2011;Kim & Shin, 2016;Lee Chin et al, 2014), aprendizaje de la práctica clínica (Brady et al, 2015;Elley et al, 2012;Janjua et al, 2017;Jansson et al, 2014;Kim & Shin, 2016), desarrollo de habilidades comunicativas (Elley et al, 2012;Kessler et al, 2015;Kesten, 2011;Koponen et al, 2012;Schlegel et al, 2012;Zavertnik et al, 2010), y autoeficacia (Aper et al, 2012;Janjua et al, 2017).…”
Section: Resultsunclassified
“…Se encontraron diferencias significativas entre los grupos en los siete estudios que lo evaluaron (Aper et al, 2012;Brady et al, 2015;Elley et al, 2012;Janjua et al, 2017;Jansson et al, 2014;Kessler et al, 2015), los tamaños del efecto fueron desde d=0.38 (Elley et al, 2012), demostrando que la simulación de pacientes humanos es más efectiva que la enseñanza tradicional como una forma de entrenar a los estudiantes en el aprendizaje de la medicina y la práctica de enfermería. Es importante destacar, sin embargo, que Elley et al (2012) no encontraron diferencias entre grupos significativas en diversas variables de aprendizaje de la práctica clínica, como fueron "Facilidad con la que se adopta un enfoque centrado en el paciente", "Calidad de la atención del médico generalista en comparación con la atención hospitalaria especializada" e "Interés en la práctica general", similar a Kessler et al (2015), en el que no se encontraron diferencias significativas en "habilidades técnicas".…”
Section: Aprendizaje De La Práctica Clínicaunclassified
See 2 more Smart Citations
“…11 The remaining four papers 19 22–24 reported that the improvement in students’ confidence was more than five percentage points after simulation training with a standard rectal model. According to Janjua et al , 28 a five percentage point increase in competence and confidence is considered clinically/educationally meaningful.…”
Section: Resultsmentioning
confidence: 99%